Computer Training for Students of Library Level I - Ugalde Víquez, Aracelly (1994)
This training is part of the Information Storage and Retrieval course whose purpose is for the student to acquire the knowledge in a global way, integrating the theory learned for the elaboration of bibliographic cards in the computer.